Design emocional aplicado no desenvolvimento de embalagens para chá - Carmo, Johanna Lieskow do (2012)
This work intends to discuss about applying Emotional Design fundaments in the creation and development of Packaging Design. Authors of which area involed in this process are studied: Emotional Design, Packaging Design, Graphic Design (typography, color and form), them combined create the basis of knowledge necessary to the development of a Packaging Design project. The product choosen for this project was tea and it was a key part of the project concept so there were also researched authors that wrote about the culture, habits and presence of tea in the brazillian market. International and national examples of tea packaging were analized in order to understand which elements are most explored in this kind of packaging. After all the fundamentation a concept was created to develop the object of the project that sought uto use the fundaments studied and resulted on the creation of a set of two packaging.